Estimation of Incubation Period for Oropouche Virus Disease among Travel-Associated Cases, 2024–2025 - Guagliardo, Sarah Anne J.; Martin, Stacey; Gould, Carolyn V.; Sutter, Rebekah; Jacobs, Daniel; O’Laughlin, Kevin; Huits, Ralph; Castilletti, Concetta; Staples, J. Erin (Emerging infectious diseases, 2025)
Determining the incubation period of Oropouche virus disease can inform clinical and public health practice. We analyzed data from 97 travel-associated cases identified by the Centers for Disease Control and Prevention (n = 74) or the GeoSentinel Network (n = 13) and 10 cases from published literature. Using log-normal interval-censored survival analysis, we estimated the median incubation period to be 3.2 (95% CI 2.5-3.9) days. Symptoms developed by 1.1 (95% CI 0.6-1.5) days for 5% of patients, 9.7 (95% CI 6.9-12.5) days for 95% of patients, and 15.4 (95% CI 9.6-21.3) days for 99% of patients. The estimated incubation period range of 1-10 days can be used to assess timing and potential source of exposure in patients with Oropouche symptoms. For patients with symptom onset >2 weeks after return from travel, clinicians and public health responders should consider the possibility of local vectorborne transmission or alternative modes of transmission.